2019
DOI: 10.3390/app9235096
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Fiber Laser Welding of Aluminum Alloy with Beam Oscillation

Abstract: Laser welding with beam oscillation is applied to join aluminum alloy plates in butt configuration. The effects of beam oscillating patterns on the quality of welds are compared and analyzed. The results indicate that beam oscillation can improve the weld formation and microstructure of butt joints. The circular oscillating weld has the features of fine grain and uniformly dispersed dendrites in the strengthening phase, and the porosity inhibitory effect of circular oscillation is the most obvious. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
1
Order By: Relevance
“…Laser beam oscillation at frequencies of several 100 Hz is generally known to stabilize laser welding processes. Studies have shown that circular beam oscillation produces ner grains and more homogeneously distributed dentrite structures in the weld zone compared to other oscillation mechanisms [23].…”
Section: Introductionmentioning
confidence: 96%
“…Laser beam oscillation at frequencies of several 100 Hz is generally known to stabilize laser welding processes. Studies have shown that circular beam oscillation produces ner grains and more homogeneously distributed dentrite structures in the weld zone compared to other oscillation mechanisms [23].…”
Section: Introductionmentioning
confidence: 96%
“…Aluminum alloys are an important engineering material in the automobile, rail, and aerospace industries as the overall performance meets the requirements of mechanical strength and low weight as well as due to their low density and high specific strength [1]. The surface quality is quite important for the efficient working of machine parts.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the nonuniform power distribution and to produce the desirable energy distribution over a defined surface area, a beam oscillating technique was developed-firstly for the electron beam [12] and, later, for the laser [13]. Recently, laser oscillating welding has gained growing interest, mainly in the field of welding of dissimilar metals [14] and aluminum alloys [11,[15][16][17][18], and also for other alloys such as low carbon steel [19], stainless steel [20,21], and Invar alloy [22]. During oscillating laser processing, the laser head moves along the defined path at a constant velocity, while the laser beam is oscillated at high frequency by a certain trajectory, for example, sinusoidal, square, triangular, circular, elliptical, etc.…”
Section: Introductionmentioning
confidence: 99%